Costa Rican Traditional Knowledge According to Local Experiences Plants, Animals, Medicine and Music - Ortega-Rodríguez, Manuel; Solís-Sánchez, Hugo.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book offers ten chapters dealing with Costa Rican traditional knowledge. Each chapter presents a transcription from a talk given to an interdisciplinary audience at Universidad de Costa Rica. The chapters address the links between knowledge and culture in a variety of cases, including black, indigenous and "white" knowledge in both rural and city contexts, with an emphasis on gender issues. This book is the first of its class and its transcriptions have been annotated for easier reading. All social scientists interested in Latin American culture or in cognitive topics in general will benefit from reading it.
Everyday and Ceremonial Bribri Songs -- Percussion Music of the Atlantic Coast -- Botanical Knowledge and Ethnomedicine Among the Bribri -- Zoological Classification in the Bribri Culture -- Ethnoagriculture: What Can we Learn from Farmers? -- Abortion, Sterilization and Medical Necessity in Costa Rica -- Lunar Ethnoastronomy of the Bribri -- Gender Relations in Costa Rican Traditional Knowledge.
Keywords: Anthropology; Ethnology -- Latin America; Culture; Anthropology; Latin American Culture